Constituents of doubly periodic instantons - Ford, Chris; Pawlowski, Jan M. (Arxiv, 2002)
Using the Nahm transform we investigate doubly periodic charge one SU(2) instantons with radial symmetry. Two special points where the Nahm zero modes have softer singularities are identified as constituent locations. To support this picture, the action density is computed analytically and numerically within a two dimensional slice containing the two constituents. For particular values of the parameters the torus can be cut in half yielding two copies of a twisted charge 1/2 instanton. Such objects comprise a single constituent.
Gesehen am 06.12.2017